1998
DOI: 10.1159/000018609
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adhesion Formation in Open and Laparoscopic Surgery

Abstract: The development of postoperative adhesions remains an almost inevitable consequence of visceral and gynecological surgery, appearing in 50–95% of all patients. The pathogenetical sequence from peritoneal injury, with locally released cytokines and inflammatory reaction, to permanent fibrous adhesions has been elucidated in recent years. Early and late bowel obstruction, chronic abdominal pain, and infertility are the main clinical complications, and they also increase the socio-economic costs. Laparoscopic sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 27 publications
2
58
0
4
Order By: Relevance
“…Good evidence exists supporting a reduction in adhesion formation following laparoscopic surgery for a large number of procedures [54,55,84,85]. There are potential disadvantages associated with laparoscopic procedures such as a longer duration of surgery with resulting damage to peritoneal mesothelium from the pneumoperitoneum [28,29,86,87].…”
Section: Methods Of Adhesion Reductionmentioning
confidence: 99%
“…Good evidence exists supporting a reduction in adhesion formation following laparoscopic surgery for a large number of procedures [54,55,84,85]. There are potential disadvantages associated with laparoscopic procedures such as a longer duration of surgery with resulting damage to peritoneal mesothelium from the pneumoperitoneum [28,29,86,87].…”
Section: Methods Of Adhesion Reductionmentioning
confidence: 99%
“…In the present study, artificial ascites achieved separation of the liver and gastrointestinal tract in 20 of 28 patients with a history of abdominal surgery, and in 23 of 27 patients with no previous laparotomy. Almost all patients who undergo abdominal surgery have some postoperative adhesion between abdominal organs, mainly the intestines 21,22 . Although the presence or absence of adhesions was not determined in the present study, it is possible that some of the 28 patients who had previously undergone laparotomy had adhesions between the liver and the gastrointestinal tract that prevented the separation of the organs by artificial ascites.…”
Section: Complicationsmentioning
confidence: 99%
“…The desiccation damage of the peritoneum can be prevented by moistening the gas before entry. Schäfer et al13]showed less visceral adhesions after laparoscopic versus laparotomic surgery, possibly due to more gently tissue handling with (atraumatic) clamps, fewer blood clots between the organs, and retaining of abdominal fluid, rich of tissue-type plasminogen activator, necessary for natural adhesiolysis during the 1st week after surgery. Smaller trocars might diminish the incidence of de novo adhesions and cicatricial hernias.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, clinical and experimental studies have shown fewer adhesions after laparoscopic operations as compared with the open technique [6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. …”
Section: Introductionmentioning
confidence: 99%